2018
DOI: 10.3390/horticulturae4020010
|View full text |Cite
|
Sign up to set email alerts
|

New Media Components and Fertilization to Accelerate the Growth of Citrus Rootstocks Grown in a Greenhouse

Abstract: Abstract:In Puerto Rico, oranges made up $6,452,000 of the agricultural gross income for 2014-2015. Today, citrus greening (CG) is the most aggressive disease affecting the citrus industry in the whole world. This disease causes dieback of the plant, among other symptoms, which is resulting in the reduction of citrus trees in the field across the world. Currently, it is recommended to grow citrus rootstocks in nurseries to produce disease-free trees. The objective of this investigation was to evaluate (before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…River valley soil is typically found in flood plains and has a lower silt content and a higher sand percentage. This soil contains goethite as the primary mineral (Arce and Rivera, 2018). Tepetzil has a discontinuous crystalline structure and high porosity due to the presence of clays (Vizcarra-de los Reyes, 2020).…”
Section: Plant Materials and Treatmentsmentioning
confidence: 99%
“…River valley soil is typically found in flood plains and has a lower silt content and a higher sand percentage. This soil contains goethite as the primary mineral (Arce and Rivera, 2018). Tepetzil has a discontinuous crystalline structure and high porosity due to the presence of clays (Vizcarra-de los Reyes, 2020).…”
Section: Plant Materials and Treatmentsmentioning
confidence: 99%
“…The availability and cost of ingredients of the substrates also play an important role in deciding if the substrate is suitable for commercial production. Arce and Rivera [12] evaluated different substrate mixes and quantities of fertilizers on the growth of citrus rootstocks. The results showed that different rootstocks responded differently, but rice husk substrate was not suitable for citrus tree production at the nursery level.…”
Section: Other Environmental Factors In Ceamentioning
confidence: 99%
“…large or small) have obstacles during the production stage in a protected environment (MERLIN et al, 2012). Thus, selecting the appropriate substrate can be a difficult task that requires consideration of both physical and chemical features (ARCE; RIVERA, 2018). There are various substrate possibilities on the market, all of which are made from diverse material combinations; these substrates also have formulations and characteristics that are either known or unknown to the producers (FRANCO et al, 2007;ALMEIDA et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Aluminium, magnesium, and iron are all found in vermiculite, which is a hydrated silicate. Moreover, this mineral absorbs up to five times its volume in water; its presence in substrate composition boosts water retention capacity (REZENDE et al, 2010;ARCE;RIVERA, 2018). It also has a high capacity for cation exchange, making it a great candidate (REZENDE et al, 2010).…”
Section: Introductionmentioning
confidence: 99%